2017
DOI: 10.5312/wjo.v8.i4.301
|View full text |Cite
|
Sign up to set email alerts
|

SyndesmoticInternalBraceTMfor anatomic distal tibiofibular ligament augmentation

Abstract: Reconstruction of unstable syndesmotic injuries is not trivial, and there is no generally accepted treatment guidelines. Thus, there still remain considerable controversies regarding diagnosis, classification and treatment of syndesmotic injuries. Syndesmotic malreduction is the most common indication for early re-operation after ankle fracture surgery, and widening of the ankle mortise by only 1 mm decreases the contact area of the tibiotalar joint by 42%. Outcome of ankle fractures with syndesmosis injury is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 29 publications
0
39
0
1
Order By: Relevance
“…Given that anatomic reduction of the distal tibiofibular syndesmosis is a key predictor of long-term ankle function, 23,25 the search for optimal treatment of an injured syndesmosis is ongoing. The concept of performing and augmenting repairs of specific syndesmotic ligaments has begun to receive increasing attention clinically 24,33 and in biomechanics research. 1,26 As reproduction of the native soft-tissue constraints represents the best option for reproducing original bony kinematics, this approach holds great potential for improving patient outcomes and reducing complications.…”
Section: Introductionmentioning
confidence: 99%
“…Given that anatomic reduction of the distal tibiofibular syndesmosis is a key predictor of long-term ankle function, 23,25 the search for optimal treatment of an injured syndesmosis is ongoing. The concept of performing and augmenting repairs of specific syndesmotic ligaments has begun to receive increasing attention clinically 24,33 and in biomechanics research. 1,26 As reproduction of the native soft-tissue constraints represents the best option for reproducing original bony kinematics, this approach holds great potential for improving patient outcomes and reducing complications.…”
Section: Introductionmentioning
confidence: 99%
“…Syndesmotic reduction with suture-tape augmentation of the AITFL has been described as both a standalone treatment option and as an adjunct to suture-button fixation, particularly for acute instability. 18,20,39,45 Although metal screw fixation has been the historical gold standard, recent studies have demonstrated that suture-button fixation results in either comparable or better outcomes with lower rates of syndesmotic malreduction. 7,15,17,27,41,56 However, no gold standard for the fixation of chronic syndesmotic injury presently exists, although several techniques have been described.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the InternalBrace (Arthrex, Naples, FL) for ankle lateral ligament reconstruction has been well described in the literature. 1,5,[9][10][11][12]14,25,27,38,47,50,54 Use for syndesmotic injuries may provide similar benefits and was first discussed by Mackay et al 27 in 2015 followed by the first detailed description of its use by Regauer et al 39 in 2017. Nonabsorbable suture-tape (FiberTape, Arthrex, Naples, FL) for syndesmotic augmentation has certain theoretical advantages over tendon graft and has been increasing in popularity.…”
Section: Introductionmentioning
confidence: 99%
“…Bunlardan birisi, Broström ameliyatının InternalBrace ® (Arthrex Inc., Naples, FL, USA) denilen biyokompozit iki vida arasında uygun şekilde gerilmiş kalınca bir fiber tape ip desteğinin tamiri desteklemek için kullanılmasıdır. [20][21][22][23][24] da negatif ön çekmece testi ve mükemmel stabilite bildirmişlerdir. [32] Ayak bileği artroskopisi ile ilgili olarak, artroskopik anatomi, bağ anatomisi ve güvenli alanlar ortaya kondukça, artroskopik kronik bağ tamirlerine de son yıllarda ilgi artmıştır.…”
Section: Tedavi̇ Konservatif Tedaviunclassified